+0  
 
0
869
2
avatar+134 

Ich hab wieder mal ein Problem ;-)

 

3 hoch (2x-1) = 2 hoch (x+3)

 

danke für eure hilfe!

 14.09.2015

Beste Antwort 

 #1
avatar+26286 
+14

Ich hab wieder mal ein Problem ;-)

 

3 hoch (2x-1) = 2 hoch (x+3)

 

\(\small{ \begin{array}{rcl} 3^{2x-1}&=& 2^{x+3} \qquad | \qquad \ln{()}\\ \ln{(3^{2x-1})} &=& \ln{(2^{x+3})} \\ (2x-1)\cdot \ln{(3)} &=& (x+3)\cdot \ln{(2)} \\ 2x\cdot \ln{(3)} - \ln{(3)} &=& x\cdot \ln{(2)} +3\cdot \ln{(2)} \\ 2x\cdot \ln{(3)} - x\cdot \ln{(2)} &=& \ln{(3)} +3\cdot \ln{(2)} \\ x \cdot [ 2\cdot \ln{(3)} - \ln{(2)} ] &=& \ln{(3)} +3\cdot \ln{(2)} \\ x &=& \frac{\ln{(3)} +3\cdot \ln{(2)} }{ 2\cdot \ln{(3)} - \ln{(2)}} \\ x &=& \frac{ 3.17805383035 } { 1.50407739678 } \\ \mathbf{x} & {=} & \mathbf{2.11295897216} \end{array} } \)

 

laugh

 15.09.2015
 #1
avatar+26286 
+14
Beste Antwort

Ich hab wieder mal ein Problem ;-)

 

3 hoch (2x-1) = 2 hoch (x+3)

 

\(\small{ \begin{array}{rcl} 3^{2x-1}&=& 2^{x+3} \qquad | \qquad \ln{()}\\ \ln{(3^{2x-1})} &=& \ln{(2^{x+3})} \\ (2x-1)\cdot \ln{(3)} &=& (x+3)\cdot \ln{(2)} \\ 2x\cdot \ln{(3)} - \ln{(3)} &=& x\cdot \ln{(2)} +3\cdot \ln{(2)} \\ 2x\cdot \ln{(3)} - x\cdot \ln{(2)} &=& \ln{(3)} +3\cdot \ln{(2)} \\ x \cdot [ 2\cdot \ln{(3)} - \ln{(2)} ] &=& \ln{(3)} +3\cdot \ln{(2)} \\ x &=& \frac{\ln{(3)} +3\cdot \ln{(2)} }{ 2\cdot \ln{(3)} - \ln{(2)}} \\ x &=& \frac{ 3.17805383035 } { 1.50407739678 } \\ \mathbf{x} & {=} & \mathbf{2.11295897216} \end{array} } \)

 

laugh

heureka 15.09.2015
 #2
avatar+134 
0

Besten Dank, heureka!

 15.09.2015

6 Benutzer online